Brief Report: Long-Term (96-Week) Efficacy and Safety After Switching From Tenofovir Disoproxil Fumarate to Tenofovir Alafenamide in HIV-Infected, Virologically Suppressed Adults. (1st June 2017) - Raffi, François; Orkin, Chloe; Clarke, Amanda; Slama, Laurence; Gallant, Joel; Daar, Eric; Henry, Keith; Santana-Bagur, Jorge; Stein, David K.; Bellos, Nicholaos; Scarsella, Anthony; Yan, Mingjin; et al.
Abstract : Abstract: In a double-blind, phase 3 trial, 663 HIV-infected, virologically suppressed adults were randomized to switch to tenofovir alafenamide (TAF; n = 333) vs. remain on tenofovir disoproxil fumarate (TDF; n = 330), each coformulated with emtricitabine (FTC), while continuing their third agent (boosted protease inhibitor or unboosted third agent). At week 96, 88.6% on FTC/TAF and 89.1% on FTC/TDF had HIV-1 RNA <50 copies per milliliter [adjusted difference −0.5% (95% confidence interval: −5.3 to 4.4%)]. Proteinuria, albuminuria, proximal renal tubular function, and bone mineral density improved after switching to TAF- from TDF-containing regimens. These longer-term data support FTC/TAF as a safe, well-tolerated, and durable nucleotide reverse transcriptase inhibitor backbone. Abstract : Supplemental Digital Content is Available in the Text.